Жанрові трансформації у сучасній польській і українській літературі (теоретичний аспект) - Ісаєнко, К. П. (My University, 2017)
Стаття присвячена аналву категорії жанру роману та її транс- формації' у контексті розвитку сучасного українсько-польського літературного процесу.
The articb deals with the genre in Ukrainian and Poland literature context devetopment modem siens of literature. Of novel particularly with novel as its kind in the context of popular literature. The principal aspects of genre of novel and women's novel have been grounded and the distinctive definitions that characterize genre of novel from different points of view have been revealed in this study. Modem life is a main subject of describe in the text
Keywords: жанр; автор; рецепція; genre; horizon of expectatbn